(untitled) (Research, Society and Development, 2020)
The present work aimed to verify which teaching methods are considered most effective in relation to learning in the Integrated Technical courses in Agriculture, Administration, Informatics, Automotive Maintenance and Environment of the IFMG Campus Bambuí, from the perspective of the teachers; as well as to evaluate the influence of the teacher´s profile/professional training regarding the use of different teaching-learning methods. The research was based on the application of a questionnaire and the responses of 38 teachers were obtained and analyzed. Ninety percent of teachers consider that their teaching methodologies promote the involvement of students and dynamic classes, although most of them do not innovate in the teaching method, since most believe they use more conservative than innovative methodologies (52.64%). However, 65.79% believe they are looking for new teaching methodologies, which shows an aspect of renewal on the part of the respondents. More than 80% of participants consider it challenging the use of new teaching technologies and that training in innovative methodology would help to overcome these teaching obstacles. However, 50% believe that innovative methods are not a tool that would help to overcome obstacles faced during the classroom. The work shows that teachers interviewed recognize the importance of using new teaching technologies, despite using more traditional ones. In addition, the results suggest that teachers have sought to improve teaching, but the applicability in their disciplines has not occurred in the same way, making it necessary to train them.